The enforcement of law in the preservation of the endangered marine species: dugongs and leatherbacks / Noor Aida Aminshah, Nur Hidayah Md Nor - Aminshah, Noor Aida; Md Nor, Nur Hidayah (2007)
As we are heading towards rapid growth and hasty development, there are lots of thing that has been neglected. Sometimes, we tend to forget other matters that are more important to us. To bring the issue at hand, let us look into the matter of our endangered marine species. The two species that we will be discussing are the Dugongs and turtles. They face a dramatic decline in their numbers. Recent studies have shown that these two species are heading towards extinction. It has been stated by the World Wild Life Fund (WWF) that, six of the seven species of marine turtles are listed as Endangered or Critically Endangered. In the Pacific, leatherbacks are heading towards extinction, fast, and in the Mediterranean, green turtle numbers have plummeted. However, Turtle and Marine Ecosystem Centre (TUMEC) claims that Leatherbacks will be extinct in Malaysia by year 2007. The Dugongs on the other hand are historically common in the shallow coastal waters of East Malaysia. They are hunted, particularly in Sabah. Today, sightings of Dugongs are only occasional but its' presence are in very small numbers. There are various reasons for this occurrence. As for turtles, they are seriously endangered because of human activities like egg collection, coastal and offshore development, and fishing activities. Dugongs however, have been hunted for human consumption and their habitat has been destroyed by development.